Lose the clutter, lose the weight : the six-week total-life slim down - Walsh, Peter, 1956- (Rodale, 2015)
"A recent study showed that people with cluttered homes were 77 percent more likely to be overweight or obese. Why? Organization pro Peter Walsh thinks it's because you can't make your best or the healthiest choices in a cluttered, messy, disorganized environment. But there's good news: you can change your habits, change you health, and change your life--all in just 6 weeks. [Includes] a room-by-room organizing guide, quizzes to create customizable plans, and testimonials from eight of the dozens of volunteers who followed this plan"--